Copper-Induced Activation of Trp Channels Promotes Extracellular Calcium Entry and Activation of Camk, Pka, Pkc, Pkg and Cblpk Leading to Increased Expression of Antioxidant Enzymes in Ectocarpus Siliculosus - Moenne-Munoz, A; Morales-Munoz, B; Gonzalez-Figueroa, A (Elsevier Masson SAS, 2018)
The existence of functional Transient Receptor Potential (TRP) channels was analyzed in Ectocarpus siliculosus using agonists of human TRPs and specific antagonists of TRPA1, TRPC5, TRPM8 and TRPV; intracellular calcium was detected for 60 min. Increases in intracellular calcium were observed at 13, 29, 39 and 50–52 min, which appeared to be mediated by the activation of TRPM8/V1 at 13 min, TRPV1 at 29 min, TRPA1/V1 at 39 min and TRPA1/C5 at 50–52 min. In addition, intracellular calcium increases appear to be due to extracellular calcium entry, not requiring protein kinase activation. On the other hand, 2.5 μM copper exposure induced increased intracellular calcium at 13, 29, 39 and 51 min, likely due to the activation of a TRPA1/V1 at 13 min, TRPA1/C5/M8 at 29 min, TRPC5/M8 at 39 min, and a TRPC5/V1 at 51 min. The increases in intracellular calcium induced by copper were due to extracellular calcium entry and required protein kinase activation. Furthermore, from 3 to 24 h, copper exposure induced an increase in the level of transcripts encoding antioxidant enzymes such as superoxide dismutase, ascorbate peroxidase, glutathione reductase and peroxiredoxin. The described upregulation decreased with inhibitors of CaMK, PKA, PKC, PKG and CBLPK, as well as with a mixture of TRP inhibitors. Thus, copper induces the activation of TRP channels allowing extracellular calcium entry as well as the activation of CaMK, PKA, PKC, PKG and CBLPK leading to increased expression of genes encoding antioxidant enzymes in E. siliculosus. © 2018 Elsevier Masson SAS